Pendugaan Fungsi Intensitas Proses Poisson Periodik dengan Tren Fungsi Pangkat Menggunakan Metode Tipe Kernel - Ro’fah Nur Rachmawati (Bina Nusantara University, 2011)
Stochastic process has an important role in many areas in everyday life, including the customer service process. The number of customers who come to a service center will be different for each particular time. A special form of stochastic process with continuous time and discrete state space is periodic Poisson process, which is a Poisson process with an intensity function of a periodic function. However, on the stochastic modeling of a phenomenon by a periodic Poisson process, the intensity function of the process is generally unknown. Therefore, a method is needed to infer the function. In this article, a Kernel estimator is formulated from a periodic Poisson process with a trend component in a rank function, which is divided into two cases; the identified rank function coefficient and the unidentified rank function coefficient.